Enhancing a job exposure matrix with subject-specific information to assess combined exposure to benzene, toluene, and xylene in a case-control study. - Friesen, Melissa C; Xie, Shuai; Locke, Sarah J; Baris, Dalsu; Schwenn, Molly; Rothman, Nathaniel; Johnson, Alison; Karagas, Margaret R; Koutros, Stella; Silverman, Debra T (Annals of Work Exposures & Health, 2026)
Objectives We modified an existing job-exposure matrix (CANJEM) to estimate the combined exposure to benzene, toluene, and xylene, which are highly correlated (hereafter, BTX), and integrated subject-specific occupational information to assess BTX exposure for participants in a bladder cancer case-control study. Methods We linked CANJEM to the lifetime occupational histories of subjects in a population-based case-control study of bladder cancer. We derived CANJEM-based estimates of the probability, intensity, and frequency of BTX exposure by assigning the highest rating observed among the benzene, toluene, and xylene CANJEM metrics. We used subject-specific exposure information in the occupational histories and exposure-oriented modules to refine the CANJEM-based BTX metrics when confirmatory exposure information was identified (hereafter, hybrid BTX metrics). We compared agreement between the CANJEM-based and hybrid BTX metrics at the job- and subject-level using kappa for the ordinal probability metrics and Spearman correlation for the continuous intensity and cumulative exposure metrics. Results The hybrid BTX approach increased 7% and decreased 5% of the CANJEM-based BTX probability ratings at the job-level and 16% and 7% at the subject-level, respectively. The CANJEM-based and hybrid BTX metrics identified 3.2% and 6.8% of the job records and 13% and 24% of the subjects as having a high probability of BTX exposure, respectively. The BTX-exposed subjects identified through the hybrid approach generally had lower cumulative exposures than those identified solely using CANJEM. CANJEM-based and hybrid BTX metrics had moderate agreement at the subject-level (probability: kappa = 0.62; cumulative metrics, Spearman correlation = 0.61). Conclusions Supplementing a JEM with subject-specific exposure information identified within-job exposure heterogeneity that was not captured by using only a JEM.